Sexual Education Improves Students’ Knowledge About Early Marriage Risks - Monica, Laily Prima; Ulfa, Maria; Agustina, Ika; Wibisono, Wahyu (Journal of Ners and Midwifery, 2025)
Early marriage is not an easy thing, especially if it is done at the wrong age. According to the Central Statistics Agency (BPS), in 2020 the prevalence of early marriage aged 15 - 17 years was 15.40 percent in Blitar Regency, while in Blitar City it was 8.00 percent. Providing sexual education is one way to prevent early marriage. The aim of this research was to determine the effect of sexual education on students' knowledge regarding the impact of early marriage at Public Vocational High School 1 of Kademangan. The design of this research was pre-experiment with One Group Pretest-Post-test approach. The samples in this research was 48 respondents taken by total sampling technique. The research instrument used a pretest-Post-test questionnaire. The method of delivering sexual education was by lecturing session with power points. The data analysis used the Wilcoxon Test. The statistical test results showed that the p-value was 0.000 or <0.05, meant there was an effect of sexual education on students' knowledge regarding the impact of early marriage at Public Vocational High School 1 of Kademangan. It is hoped that the results of this research can be used as evaluation material and information to support increased knowledge of the impact of early marriage on teenagers which can be conveyed by institutions.